2016
DOI: 10.5146/tjpath.2015.01343
|View full text |Cite
|
Sign up to set email alerts
|

Twist expression in pleomorphic adenoma, adenoid cystic carcinoma and mucoepidermoid carcinoma of salivary glands

Abstract: Objective: Twist is an important transcription factor that induces epithelial-mesenchymal transition and therefore plays an important role in tumor progression. There are a few studies on Twist expression in salivary gland carcinomas. The aim of this study was to evaluate and compare the expression of Twist in the most common benign and malignant salivary gland tumors and to determine whether its expression was correlated with any tumor characteristics.Material and Method: in this retrospective cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 24 publications
2
14
1
Order By: Relevance
“…Zhou et al (2012) observed that overexpression of Twist induces EMT-like transformation of the metastatic cell lines of human SACC, with enhancing the migration and invasion abilities of these cells [ 32 ]. Pardis et al (2016) recorded a high Twist expression in malignant salivary gland tumors, including ACC compared to normal glands and benign tumors, but they did not find any correlation with the size, stage or grade of tumor [ 33 ]. However, the authors proved the existence of a relationship between nuclear Twist expression and increasing tumor invasiveness in SACC, confirming the invasive behavior of these tumors.…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…Zhou et al (2012) observed that overexpression of Twist induces EMT-like transformation of the metastatic cell lines of human SACC, with enhancing the migration and invasion abilities of these cells [ 32 ]. Pardis et al (2016) recorded a high Twist expression in malignant salivary gland tumors, including ACC compared to normal glands and benign tumors, but they did not find any correlation with the size, stage or grade of tumor [ 33 ]. However, the authors proved the existence of a relationship between nuclear Twist expression and increasing tumor invasiveness in SACC, confirming the invasive behavior of these tumors.…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…One study, recently, reported that Twist expression contributed to the invasiveness of salivary SACC (Shen et al 2010) and Twist may also be linked to perineural tumor invasiveness (Zhou et al 2012). High levels of Twist were shown also in MEC, confirming the emerging role of this protein in carcinogenesis of the salivary glands and also in malignant transformation and tumor invasiveness (Pardis et al 2016).…”
Section: Prognostic Relevance Of Emt In Sgs' Malignanciesmentioning
confidence: 91%
“…The occurrence of EMT within PA has been demonstrated by immunohistochemical and ultrastructural analyses [ 48 , 58 , 59 ], but no specific TFs have been identified. To our knowledge, only four studies have investigated the expression of EMT-TFs in PAs through the examination of TWIST or SLUG expression by immunohistochemical or reverse transcription-quantitative polymerase chain reaction (RT–qPCR) analysis [ 60 , 61 , 62 , 63 ].…”
Section: Emt-activating Transcription Factors (Emt-tfs) In Pasmentioning
confidence: 99%
“…Pardis et al [ 60 ] reported observing TWIST expression in 12 cases of PA, predominantly with a cytoplasmic pattern and moderate intensity, evaluated immunohistochemically. Furthermore, Yuen et al [ 64 ] reported that the cytoplasmic expression of TWIST was associated with neoplastic transformation in prostate tissues.…”
Section: Emt-activating Transcription Factors (Emt-tfs) In Pasmentioning
confidence: 99%
See 1 more Smart Citation